Transport, constructability, and economic advantages of SMR modularization - Lloyd, Clara A.; Roulstone, Tony; Lyons, Robbie E. (Progress in nuclear energy (New series), 2021)
This paper presents an offsite modular construction approach, subject to transport constraints, for nuclear power plants. The modular construction principles underlying this work are generalizable across different reactor types; however, this paper focuses only on Small Modular Reactors (SMRs) that are of the Pressurized Water Reactor (PWR) type. Existing work on large nuclear reactor modularization is used to generate a module breakdown scheme for both small and large reactors and a module reconfiguration strategy is proposed that allows modules to fit within road transportable weight and dimension limits. Fully modularized SMRs can transport approximately 80% of their modules by road, compared to only 20% for large reactors. This has a significant effect on cost: a first-of-a-series, fully modular 300 MWe SMR can reduce overnight construction costs to $5470/kWe, a 45% reduction relative to its conventionally-built counterpart. This suggests that by using a standard design and radical modularization, SMRs could compete with current large reactor baseline construction costs of $6100/kWe. Standardization, another aspect of modular manufacturing best-practise, serves to remove repeat design costs and lowers nuclear construction costs by 15%. Additionally, SMRs can further reduce costs through shorter build schedules and production learning. These findings emphasize the importance of modularization for small reactor economics, highlighting the need for further research into the issues surrounding modularization, factory-centered offsite build, and supply chain strategy for small reactors. Transportable weight fraction of modules on an overall basis (lines) and sorted by module type (points). [Display omitted] •Manufacturing principles can improve nuclear economics and programme management.•Addressing and resolving transport issues is key to enabling SMR modularization.•Design standardisation and modularization mean SMRs can compete with large reactors.